PENGARUH PROMOSI DI MEDIA SOSIAL, FEAR OF MISSING OUT (FOMO), DAN SELF-CONTROL TERHADAP PERILAKU IMPULSIVE BUYING PADA GENERASI Z DALAM PERSPEKTIF EKONOMI SYARIAH - Putri, Natasya; Yustati, Herlina; Hartini, Kustin (LPPM - STIE SAKTI ALAM KERINCI, 2026)
The purpose of this study is to determine how much influence the influence of promotions on social media, fear of missing out (FOMO), and self-control on impulsive buying behavior in generation Z in the perspective of Islamic economics. This study uses a quantitative method with primary data collection techniques in the form of questionnaires distributed to 140 respondents. The sample in this study was gen z aged 17-29 years, domiciled in Tengah Padang village and shopee users. The data analysis technique used is Partial Least Square analysis with the help of the Smartpls application. The results of the study show that partially promotions on social media, fear of missing out (FOMO) have a positive and significant effect on impulsive buying, and self-control has a negative and significant effect on impulsive buying. Simultaneously, promotions on social media, FoMO, and self-control have a significant effect on impulsive buying with an R-Square value of 0.585.